1992
DOI: 10.1172/jci116020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for tissue-specific activation of renal angiotensinogen mRNA expression in chronic stable experimental heart failure.

Abstract: The intrarenal renin-angiotension system (RAS) may contribute to the pathophysiology of heart failure by the generation of angiotensin II at local sites within the kidneys. Angiotensin II may directly influence renal hemodynamics, glomerular contractility, and tubular sodium reabsorption, thereby promoting sodium and fluid retention in this syndrome. In the present study, we examined components of the circulating RAS as well as the intrarenal expressions of renin and angiotensinogen mRNA in rats with stable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 40 publications
1
39
1
Order By: Relevance
“…The tyrosine kinase inhibitor genistein significantly decreased both All-and PMA-stimulated PAI-2 expression in both RASMC and RME cells. Tyrosine kinase inhibitors have been shown to block the endothelin-l-stimulated induction of cfos and activation of AP-1 cis-element activity in glomerular mesangial cells (51). Since Cousins et al (35) have shown that two AP-1 binding sites in the 5' flanking region of the PAI-2 promoter are required for the PKC-stimulated transcription of PAI-2, this effect of tyrosine kinase inhibition by genistein may also apply to the PKC-dependent mechanism of All-stimulated PAI-2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The tyrosine kinase inhibitor genistein significantly decreased both All-and PMA-stimulated PAI-2 expression in both RASMC and RME cells. Tyrosine kinase inhibitors have been shown to block the endothelin-l-stimulated induction of cfos and activation of AP-1 cis-element activity in glomerular mesangial cells (51). Since Cousins et al (35) have shown that two AP-1 binding sites in the 5' flanking region of the PAI-2 promoter are required for the PKC-stimulated transcription of PAI-2, this effect of tyrosine kinase inhibition by genistein may also apply to the PKC-dependent mechanism of All-stimulated PAI-2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…kidney vessels; angiotensin-converting enzyme; laser microcapture THE RENIN-ANGIOTENSIN SYSTEM (RAS) plays a key role in the control of cardiovascular and renal function (8,13,30). Activation of the RAS has been widely incriminated in the pathophysiology of renal and cardiovascular diseases such as hypertension, myocardial infarction, and heart failure (21,25). The RAS system primarily involves two enzymes: renin, which cleaves angiotensinogen to the inactive decapeptide angiotensin (ANG) I, and angiotensin-converting enzyme (ACE), a dipeptidyl carboxypeptidase that hydrolyzes ANG I to the octapeptide ANG II (7,26).…”
mentioning
confidence: 99%
“…These changes comprise both protein and mRNA level. Numerous studies have shown that MI has a significant impact on changes in the RAS system components, such as expression of angiotensin receptors, or angiotensin-converting enzyme activity in various tissues [7,[34][35][36]. In vivo and in vitro experiments have shown that MI provokes a dramatic up-regulation of both angiotensin receptor subtypes in different organs [34,37,38].…”
Section: Discussionmentioning
confidence: 99%